Fantasy Formula in Romance Movies: Beauty and the Beast (2017) and Aladdin (2019) - Kartika, Yuri Yusnia; Saehu, Andang; Pramita, Agry (STAIN Sultan Abdurrahman Kepulauan Riau, 2022)
Popular literature is an entertaining work and is widely loved by the public. This study focuses on formula analysis of fantasy genres identified from the Beauty and the Beast (2017) and Aladdin (2019) movies seen from several scenes in both movies. The films is an interesting fantasy genre movies because although the movies is different, it has the same formula. This research uses a comparative descriptive method with a qualitative approach to present data analysis. In addition, this study also used several theories from Saricks (2009) to examine the formula of the fantasy genre and the theory of comparative literature from Wellek and Warren's (1942). The study reveals that there are four points of the fantasy genre formula that have something in common in these two movies. First, in the Characteristics of Belle and Jasmine who are brave women and have an adventurous spirit. Second, the same Storyline between the two movies where both are the same against enemies who want to kill the main male characters. Third, the same Frame Setting contains magical elements. Finally, in both movies there are tense scenes that quickly turn into humorous scenes or in the fantasy genre formula called Pacing. From the results obtained by the researchers, it was concluded that in both movies there are elements of fantasy formula. These formulas then make fantasy movies into films that are great demand and liked by the audience.